1966
DOI: 10.1111/j.1651-2227.1966.tb15219.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Streptococcus Group A Infection: The Carrier State and Latent Infection among Childen

Abstract: Summary A longitudinal study has been conducted on 114 children in a hospital for primary tuberculosis, in order to determine the incidence of Group A latent streptococcal infection. The subjects were regularly examined for the presence of Group A streptococcus in the throat, the level of streptococcal antibodies in the sera; a daily methodical investigation was also performed in the search of any clinical symptoms of infection. The analysis of the modes of infection shows that several degrees exist between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1970
1970
1988
1988

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The ASO titre may be found to be raised in apparently normal individuals; in one study (Lawy 1960) 12% of sera examined showed ASO titres of 200 u./ml. Subclinical infections with Group A streptococci do occur (Rantz 1945, Mozziconacci et al 1966 and it is assumed that this may account for some, perhaps all, instances in which ASO titre has unexpectedly been found to be high.…”
mentioning
confidence: 99%
“…The ASO titre may be found to be raised in apparently normal individuals; in one study (Lawy 1960) 12% of sera examined showed ASO titres of 200 u./ml. Subclinical infections with Group A streptococci do occur (Rantz 1945, Mozziconacci et al 1966 and it is assumed that this may account for some, perhaps all, instances in which ASO titre has unexpectedly been found to be high.…”
mentioning
confidence: 99%